Water-holding and water-holding capacity of meat and methods of its determination - L. S. Kudryashov; O. A. Kudryashova (Теория и практика переработки мяса, 2023)
The considered topic is of great interest for researchers and practitioners engaged in the development of technology and the production of meat food. In the review, the authors focus on theoretical aspects of the meat capacity to bind and hold water. The characteristic of the forms and strength of the water-to-meat bonds is given. The influence of the structural elements of muscle tissue on the meat capacity to bind and hold water is shown. The different opinions of the specialists are given in regard to the terms “water-binding” (WBC) and “water-holding” (WHC) capacity of meat, and the authors of this research expressed their own opinion. Basing on the analysis of publications, a characteristic is given to forms of water-to-meat bonds strength from the point of view of technological practice: there is tightly bound water, loosely bound available water (immobilized), and loosely bound excessive water (free). The article summarizes the material on the methods of determination of water-holding (water-binding) capacity of meat. It is shown that up to date there is no unequivocal answer about the choice of WHC determination method. To define WHC, it is recommended to subtract the WBC value obtained by one of the gravimetric methods from the value of the indicator obtained by one of the methods of external pressure. This problem requires further research, discussion of issues and methods for determination of water-holding capacity.